Oxford practice grammar : advanced : with answers. - Yule, George, 1947- (Oxford : University Press, 2006)
This new three-level series edition offers just the right balance of explanations and practice. The Advanced level offers in-depth explanations and challenging activities to help students refine their grammatical competence. The Grammar Practice-Plus CD-ROM expands on materials covered in the texts. Listen and Speak: Students hear sentences, select the correct response, and record their own voices. Read and Write: Students practice identifying errors and correcting them. Test and Review: Multiple choice tests help students check their progress.
Keywords: Engelse spraakkunst